Experiences of Patients With Auditory Processing Disorder in Getting Support in Health, Education, and Work Settings: Findings From an Online Survey - Agrawal, Deepashri; Dritsakis, Giorgos; Mahon, Merle; Mountjoy, Alyson; Bamiou, Doris E. (Frontiers in Neurology, 2021)
Objective: To explore the views and experiences of individuals with Auditory Processing Disorder (APD) and/or their families in getting support from services and to receive their suggestions for improvement. Design: Cross-sectional random sample survey with descriptive analysis. Settings: Online survey. Participants: 156 individuals with APD and/or their family members from the APD Support UK patient support organisation and four associated APD Facebook groups. Main outcome measure: A 16-item questionnaire on negative and positive experiences in getting a referral for diagnosis, funding for the FM system, and overall support for APD. Results: The key findings that emerged included reports of difficulty in getting a referral for diagnosis (54%), obtaining funding for an FM system (45%), getting support for APD (61%), and poor recognition and awareness of APD (63%) in Education, Health or Work settings. The positive experiences reported were ease in getting a referral for diagnosis (46%), in obtaining an FM system (20%), and with diagnosis leading to help at school or to a better understanding of the condition and the required adjustments. The recommended improvement areas were raising awareness of APD and related management in Education (30%), the Health sector (25%), and the public (18%). Conclusions: Individuals and families of individuals with APD overwhelmingly report a lack of awareness of APD across health, education, and work sectors, and difficulties in getting access to diagnosis and support. This information may provide an initial understanding of the patients’ needs for clinical services for APD, identify research priorities, and influence longer-term public health decisions towards improved care.